Cranial and cerebral signs in the diagnosis of spina bifida between 18 and 22 weeks of gestation: a German multicentre study - Bahlmann, F.; Reinhard, I.; Schramm, T.; Geipel, A.; Gembruch, U.; Von Kaisenberg, C. S.; Schmitz, R.; Stupin, J.; Chaoui, R.; Karl, K.; Kalache, K.; Faschingbauer, Florian; et al. (Prenatal Diagnosis, 2015)
The aim of this article is to study secondary cranial signs in fetuses with spina bifida in a precisely defined screening period between 18 + 0 and 22 + 0 weeks of gestation.On the basis of retrospective analysis of 627 fetuses with spina bifida, the value of indirect cranial and cerebral markers was assessed by well-trained ultrasonographers in 13 different prenatal centres in accordance with the ISUOG (International Society of Ultrasound in Obstetrics and Gynecology) guidelines on fetal neurosonography.Open spina bifida was diagnosed in 98.9% of cases whereas 1.1% was closed spina bifida. Associated chromosomal abnormalities were found in 6.2%. The banana and lemon signs were evident in 97.1% and 88.6% of cases. Obliteration of the cisterna magna was seen in 96.7%. Cerebellar diameter, head circumference and biparietal diameter were below the 5th percentile in chromosomally normal fetuses in 72.5%, 69.7% and 52%, respectively. The width of the posterior horn of the lateral ventricle was above the 95th percentile in 57.7%. The secondary cranial and cerebral signs were dependent on fetal chromosome status and width of the posterior horn. Biparietal diameter was also dependent on the chromosome status with statistical significance p = 0.0068. Pregnancy was terminated in 89.6% of cases.In standard measuring planes, lemon sign, banana sign and an inability to image the cistern magna are very reliable indirect ultrasound markers of spina bifida. © 2014 John Wiley & Sons, Ltd.
EVALuna2:17644